Advancing the Sea Ice Hypothesis: Trophic Interactions Among Breeding Pygoscelis Penguins With Divergent Population Trends Throughout the Western Antarctic Peninsula - Gorman, Kristen B.; Ruck, Kate E.; Williams, Tony D.; Fraser, William R. (Frontiers in Marine Science, 2021)
We evaluated annual and regional variation in the dietary niche of Pygoscelis penguins including the sea ice-obligate Adélie penguin (Pygoscelis adeliae), and sea ice-intolerant chinstrap (Pygoscelis antarcticus) and gentoo (Pygoscelis papua) penguins, three species that nest throughout the western Antarctic Peninsula (AP) to test the sea ice trophic interaction hypothesis, which posits that penguin breeding populations with divergent trends, i.e., declining or increasing, are reliant on differing food webs. Our study relies on values of naturally occurring carbon (13C/12C, δ13C) and nitrogen (15N/14N, δ15N) stable isotopes as integrated proxies of penguin food webs measured over three years at three different breeding colonies. At Anvers Island in the north, where reductions in sea ice and changes in breeding population trends among sympatric sea ice-obligate (Adélie) and sea ice-intolerant (chinstrap and gentoo) penguins have been most notable, our analyses show that all three species of Pygoscelis penguins became more similar isotopically over the reproductive period. By late chick-rearing at Anvers Island, crèched chicks at 5-weeks-old for all species occupied similar trophic positions. Isotopic mixing models indicated that the proportions of prey provisioned by adult penguins to 5-week-old chicks at Anvers Island were generally similar across species within years, consisting primarily of Antarctic krill (Euphausia superba). Crèched Adélie chicks had higher δ13C and δ15N values at Avian and Charcot Islands, southern breeding colonies where sea ice is more prominent and populations of Adélie penguins have increased or remain stable. Trophic position increased with latitude, while the proportions of prey provisioned by Adélie penguin adults to chicks at southern breeding colonies included species typical of high Antarctic marine food webs, especially crystal krill (Euphausia crystallorophias). A Bayesian metric for dietary niche width, standard ellipse area (SEA-B), indicated that Pygoscelis penguins with greater population changes in the north had more variability in dietary niche width than stable populations further south. Our results lend insight on marine food web drivers of Pygoscelis penguin reproduction at the regional scale and question the long-standing paradigm that Antarctic krill are the only food web component critical to penguin reproductive survival in this region of the Southern Ocean.